2021
DOI: 10.1002/adfm.202102237
|View full text |Cite
|
Sign up to set email alerts
|

Copolymer‐Templated Nickel Oxide for High‐Efficiency Mesoscopic Perovskite Solar Cells in Inverted Architecture

Abstract: Despite the outstanding role of mesoscopic structures on the efficiency and stability of perovskite solar cells (PSCs) in the regular (n–i–p) architecture, mesoscopic PSCs in inverted (p–i–n) architecture have rarely been reported. Herein, an efficient and stable mesoscopic NiOx (mp‐NiOx) scaffold formed via a simple and low‐cost triblock copolymer template‐assisted strategy is employed, and this mp‐NiOx film is utilized as a hole transport layer (HTL) in PSCs, for the first time. Promisingly, this approach al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 62 publications
1
51
0
1
Order By: Relevance
“…TiO 2 nanorods serve as scaffolds in the perovskite solar cells, resulting in the full coverage of perovskite capping layers and thereby achieving a more efficient charge separation and lower charge recombination. Similarly, mesoporous NiO x as a hole transport layer of perovskite solar cells can be also fabricated via the BCP template-assisted method (Sadegh et al, 2021). In these perovskite solar cells, the high-quality mesoporous NiO x structure can significantly inhibit charge recombination and promote charge transportation, leading to a high PCE of 20.2%.…”
Section: Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 nanorods serve as scaffolds in the perovskite solar cells, resulting in the full coverage of perovskite capping layers and thereby achieving a more efficient charge separation and lower charge recombination. Similarly, mesoporous NiO x as a hole transport layer of perovskite solar cells can be also fabricated via the BCP template-assisted method (Sadegh et al, 2021). In these perovskite solar cells, the high-quality mesoporous NiO x structure can significantly inhibit charge recombination and promote charge transportation, leading to a high PCE of 20.2%.…”
Section: Solar Cellsmentioning
confidence: 99%
“…During the past 20 years, BCP self-assembly achieved great progress and created immense interest in semiconductor fabrication. To date, templates for BCP selfassembly were mainly used in the manufacture of nonvolatile memory devices (Guarini et al, 2003;Yoo et al, 2015), bitpatterned media (BPM) (Xiao et al, 2009;Griffiths et al, 2013), fin field-effect transistors (FinFETs) (Black, 2005;Liu et al, 2018), photonic nanodevices (Stefik et al, 2015;Alvarez-Fernandez et al, 2021), solar cells (Topham et al, 2011;Sadegh et al, 2021), chemical and biological sensors (Jeong et al, 2014;Kang et al, 2020), and ultrafiltration membranes (Jackson and Hillmyer, 2010;Guo et al, 2021), as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…In MPSC, the compact layer is deposited on a fluorine doped tin oxide layer (FTO), which usually blocks holes and extracts electrons [1]. A typical MPSC involves nanoscale pores in ETL scaffold [39]. First, the absorber layer covers the ETL, makes a compact capping layer, and then penetrates it which forms an intermixed layer.…”
Section: Mesoporous Perovskite Solar Cell (N-i-p)mentioning
confidence: 99%
“…The hole transport layer (HTL) has played a dominant role in the device performance and long-term stability of inverted perovskite solar cells (PSCs). [1][2][3][4][5][6] At present, various organic hole transport materials (HTMs) have been applied, especially poly (3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) and poly(bis(4phenyl)(2,4,6-trimethylphenyl)amine) (PTAA). However, their complicated fabrication process, intrinsic chemical volatility, poor stability, and high cost hinder the large-scale application toward commercialization.…”
Section: Introductionmentioning
confidence: 99%